2018
DOI: 10.1016/j.matchar.2017.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of thin films prepared by co-sputtering iron and titanium precursors and thermal oxidation under air atmosphere

Abstract: Nanocomposites of metal oxides are useful materials for operation in many energy conversion systems. In this study, such nanocomposites were prepared by oxidation of mixtures of iron and titanium precursor metallic thin films at 520 °C under air atmosphere. The metallic films with different iron percentages were obtained by radio frequency (RF) magnetron sputtering on glass and silicon substrates. The films were characterized by means of X-Ray Diffraction (XRD), Raman spectroscopy, UV-vis spectroscopy, High Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The as-deposited TiO 2 film was found to have an amorphous structure, as indicated by the absence of any peak’s characteristic of the TiO 2 phase. Upon annealing at 600 °C, either in vacuum or under NH 3 flow, TiO 2 film crystallization occurred from the amorphous to the anatase phase; indeed, the Raman spectra evidenced peaks positioned at 142.3, 394.4, and 634.9 cm −1 that may be assigned to the E g and B 1g vibration modes of the anatase structure [ 26 , 27 ]. Although the A 1g /B 1g vibration mode located in the 513–519 cm −1 range cannot be distinguished because of an overlap with the Si substrate peak, there is indeed in this wavelength a region peak broadening to varying extents, indicating the anatase phase formation.…”
Section: Resultsmentioning
confidence: 99%
“…The as-deposited TiO 2 film was found to have an amorphous structure, as indicated by the absence of any peak’s characteristic of the TiO 2 phase. Upon annealing at 600 °C, either in vacuum or under NH 3 flow, TiO 2 film crystallization occurred from the amorphous to the anatase phase; indeed, the Raman spectra evidenced peaks positioned at 142.3, 394.4, and 634.9 cm −1 that may be assigned to the E g and B 1g vibration modes of the anatase structure [ 26 , 27 ]. Although the A 1g /B 1g vibration mode located in the 513–519 cm −1 range cannot be distinguished because of an overlap with the Si substrate peak, there is indeed in this wavelength a region peak broadening to varying extents, indicating the anatase phase formation.…”
Section: Resultsmentioning
confidence: 99%
“…Iron oxide can be found in various phases such as magnetite, wustite, and trioxide (α-Fe 2 O 3 , β-Fe 2 O 3 , γ-Fe 2 O 3 , and ϵ-Fe 2 O 3 ), among others, depending on preparation methods. Haematite, maghemite, and magnetite are iron oxides [26].…”
Section: Resultsmentioning
confidence: 99%
“…[13,14] At room temperature rutile has a bandgap of 3.06 eV, [15] 3.3 eV for brookite, and a wide bandgap of about 3.4 eV for anatase phase. [16] Several attempts have been made to fabricate the doped TiO 2 nanostructures using various synthetic routes and to study the variation in their physical and chemical properties because in facilitating advanced technologies, the critical parameters such as the morphology and phase composition determine their suitability for multiple applications. [9] Bernard et al [17] in their shape-dependent thermodynamic model reported that both the shape and phase stability of TiO 2 nanoparticles strongly depend on their surface chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, doping of TiO 2 with transition metals/nonmetals has been widely investigated for a wide range of applications such as photocatalysis, water splitting, and N 2 reduction reaction, etc. [18][19][20] For instance, doping TiO 2 with metals/non-metals such as carbon, [21] nitrogen, [22] sulfur, [23] vanadium, [15] manganese, [16] iron, [17] nickel, [18] etc. has been reported to modify the bandgap of TiO 2 and extend its absorption to the visible region for photocatalysis.…”
Section: Introductionmentioning
confidence: 99%